2000
DOI: 10.1038/sj.bjp.0703637
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor‐α stimulates prostaglandin generation through cytosolic phospholipase A2 under the control of p11 in rat gastric epithelial cells

Abstract: 1 The regulatory e ects of transforming growth factor (TGF)-a on phospholipase A 2 (PLA 2 ) isozymes contributing to prostaglandin generation in rat gastric epithelial RGM1 cells were examined.2 Stimulation with TGF-a for 24 h time-dependently induced prostaglandin E 2 generation with an increase in cyclo-oxygenase-2 protein. The TGF-a-induced prostaglandin E 2 generation was suppressed by NS-398, a cyclo-oxygenase-2 inhibitor. 3 TGF-a stimulated the activity and the protein synthesis of cytosolic PLA 2 (cPLA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 26 publications
(37 reference statements)
2
24
0
Order By: Relevance
“…13 shows a summary of the pathway of arachidonate release and PGE 2 production in cytokine-stimulated RGM1 cells. TGF-␣ and IL-1␤ act synergistically to promote PGE 2 production, as first reported by Akiba et al (15,28), and we also report that these two cytokines lead to a synergistic release of arachidonate. A delayed phase of arachidonate release (12-24 h) occurs concomitantly with a large increase in the amount of mRNA for group IIA sPLA 2 and the appearance of group IIA sPLA 2 protein in the culture medium.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…13 shows a summary of the pathway of arachidonate release and PGE 2 production in cytokine-stimulated RGM1 cells. TGF-␣ and IL-1␤ act synergistically to promote PGE 2 production, as first reported by Akiba et al (15,28), and we also report that these two cytokines lead to a synergistic release of arachidonate. A delayed phase of arachidonate release (12-24 h) occurs concomitantly with a large increase in the amount of mRNA for group IIA sPLA 2 and the appearance of group IIA sPLA 2 protein in the culture medium.…”
Section: Discussionsupporting
confidence: 65%
“…Lipids were extracted twice with 2 ml of ethyl acetate, and ethyl acetate was evaporated under a nitrogen stream. Samples were spotted onto a aluminum-back silica gel plate (20 ϫ 20 cm) with small amounts of ethyl acetate and separated by thin layer chromatography using the upper phase of ethyl acetate/isooctane/ acetic acid/H 2 O (9:5:2:10, v/v) (15,28). Authentic PGE 2 was added to each sample before spotting, and the plate was placed in a glass tank containing I 2 to visualize the PGE 2 -containing plate region.…”
Section: Materials-[mentioning
confidence: 99%
“…Annexin family proteins have been studied in different cell types, such as epithelial (Yao et al 1999, Akiba et al 2000, endothelial (Hajjar & Acharya 2000, Deora et al 2004, and skeletal and smooth muscle cells (Babiychuk et al 1999, Draeger et al 2005. Even though the cell biology of annexin 2 and p11 has been extensively studied at the molecular and cellular levels in various Figure 4 Western blot analysis of cytosolic annexin 2 (A2) protein (A) in pregnant sheep myometrium collected from controls treated with vehicle (Cont, lanes 1-6), progesterone (P, lanes 7-11), estradiol and progesterone (EP, lanes 12-16), and estradiol (E, lanes 17-22) at 121 dGA.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, annexin 2 has been suggested to function in membrane organization and traffic (Babiychuk & Draeger 2000, Draeger et al 2005, endocytosis and exocytosis (Zobiack et al 2003), tight junction assembly (Lee et al 2004), regulation of plasma membrane ion channels (Girard et al 2002, Okuse et al 2002, Poon et al 2004, and in lipid-related cellular signaling (Wu et al 1997a, Huang et al 2002. p11 has been shown to regulate prostaglandin production by altering cPLA2 activity and release of arachidonic acid in rat gastric epithelial cells (Akiba et al 2000). Therefore, the heterotetramer of annexin 2 and p11 could be an important mediator in Ca 2C signaling and prostaglandin synthesis in uterine smooth muscles.…”
Section: Introductionmentioning
confidence: 99%
“…Dexamethasone, a glucocorticoid, reduced cPLA 2 ␣ activity by up-regulation of p11 in human epithelial cells (39). It was also reported that transforming growth factor-␣ inhibited A23187-induced AA release by increasing p11-cPLA 2 ␣ binding (40,41). Collectively, these data suggest that p11 may play a role in regulating cPLA 2 ␣ activity and AA release.…”
mentioning
confidence: 52%